2004
DOI: 10.18773/austprescr.2004.096
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of antiepileptic drugs in seizure-free adults

Abstract: SummaryWhether or not antiepileptic drugs should be withdrawn after a patient has been seizure-free for several years is a complex issue. Some studies suggest the overall risk of seizure recurrence is approximately 30% if treatment is withdrawn. Clinical factors associated with a greater chance of successful withdrawal include childhood onset epilepsy, a normal electroencephalogram prior to drug withdrawal, being seizure-free for more than two years, monotherapy, normal neuroimaging and normal intellect. If an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…The most common reason for relapse was poor adherence to AED therapy. 4 The present study showed that a high proportion of patients were taking a single AED at the last follow-up. In addition to simple forgetfulness, many teenagers may feel stigmatized by taking an AED therapy.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The most common reason for relapse was poor adherence to AED therapy. 4 The present study showed that a high proportion of patients were taking a single AED at the last follow-up. In addition to simple forgetfulness, many teenagers may feel stigmatized by taking an AED therapy.…”
Section: Discussionmentioning
confidence: 48%
“…For example, childhood absence epilepsy shows a good prognosis for AED discontinuation, while juvenile myoclonic epilepsy, which is common in adolescence, is associated with a high risk of recurrence. 4 The present study showed that a high proportion of patients were taking a single AED at the last follow-up. Furthermore, more than half of these final monotherapies were newer AEDs such as lamotrigine and levetiracetam.…”
Section: T a B L Ementioning
confidence: 48%
“…Frekuensi terbanyak pada tipe tonik klonik umum, sesuai dengan penelitian Fukushima (1981) yang menyatakan bahwa kekambuhan banyak dijumpai pada epilepsi tipe umum, hal ini mungkin akibat adanya epileptiform discharge yang sinkron bilateral dan simetris mengenai kedua hemisfer (Kilpatrick CJ. 2004).…”
Section: Hasil Dan Pembahasanunclassified
“…Risiko relatif yang didapat yaitu 1,957 (95% CI, 1,357-2,822) menunjukkan bahwa terjadinya kekambuhan pada penderita epilepsi dengan gambaran EEG abnormal sebesar 1,957 kali dibandingkan yang dengan EEG normal. Kilpatrick (2004) menyatakan penelitian yang dilakukan MRC (Medical Research Council) menemukan bahwa pasien dengan bangkitan tonik klonik dan gambaran EEG generalised spike wave mempunyai angka kekambuhan yang tinggi.…”
Section: Hasil Dan Pembahasanunclassified
“…23 However, a Cochrane review has highlighted the lack of evidence to guide clinicians on the optimal rate of withdrawal in patients whose seizures are well controlled. 24 There is little evidence to guide antiepileptic drug withdrawal tapering periods in nonepileptic patients.…”
Section: Withdrawalmentioning
confidence: 99%